The blood-brain barrier and methamphetamine: open sesame? - Turowski, Patric; Kenny, Bridget-Ann (Frontiers in Neuroscience, 2015)
The chemical and electrical microenvironment of neurons within the central nervous system is protected and segregated from the circulation by the vascular blood–brain barrier. This barrier operates on the level of endothelial cells and includes regulatory crosstalk with neighbouring pericytes, astrocytes and neurons. Within this neurovascular unit, the endothelial cells form a formidable, highly regulated barrier through the presence of inter-endothelial tight junctions, the absence of fenestrations, and the almost complete absence of fluid-phase transcytosis. The potent psychostimulant drug methamphetamine transiently opens the vascular blood–brain barrier through either or both the modulation of inter-endothelial junctions and the induction of fluid-phase transcytosis. Direct action of methamphetamine on the vascular endothelium induces acute opening of the blood-brain barrier. In addition, striatal effects of methamphetamine and resultant neuroinflammatory signalling can indirectly lead to chronic dysfunction of the blood-brain barrier. Breakdown of the blood-brain barrier may exacerbate the neuronal damage that occurs during methamphetamine abuse. However, this process also constitutes a rare example of agonist-induced breakdown of the blood-brain barrier and the adjunctive use of methamphetamine may present an opportunity to enhance delivery of chemotherapeutic agents to the underlying neural tissue.